2019
DOI: 10.1038/s41598-019-50134-y
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Eucalyptus oil nanoemulsion by micellar nanotechnology: transdermal analgesic activity using hot plate test in rats’ assay

Abstract: Eucalyptus globulus is an aromatic medicinal plant which known for its 1,8-cineole main pharmacological constituent exhibits as natural analgesic agent. Eucalyptus globulus-loaded micellar nanoparticle was developed via spontaneous emulsification technique and further evaluation for its analgesic efficacy study, in vivo analgesic activity assay in rats. The nanoemulsion system containing Eucalyptus-micelles was optimized at different surfactant types (Tween 40, 60 and 80) and concentrations (3.0, 6.0, 9.0, 12.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 49 publications
4
28
0
Order By: Relevance
“…It is an aromatic medicinal plant with main pharmacological constituent 1,8-cineole ( Yadav and Chandra, 2017 ) also known as eucalyptol ( de Cássia da Silveira e Sá et al, 2013 ). Independent studies have reported anti-inflammatory properties of eucalyptus oil (EO) and its principle component eucalyptol (1,8- cineole) ( Santos and Rao, 2000 ; Silva et al, 2003 ; Sadlon and Lamson, 2010 ; Yadav and Chandra, 2017 ), which, depending on the source species of eucalyptus, accounts for up to 75% of eucalyptus oil’s content ( Aziz et al, 2019 ). Essential oils of various eucalyptus species are utilized in the cosmetic, food, and pharmaceutical industries ( Marzoug et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is an aromatic medicinal plant with main pharmacological constituent 1,8-cineole ( Yadav and Chandra, 2017 ) also known as eucalyptol ( de Cássia da Silveira e Sá et al, 2013 ). Independent studies have reported anti-inflammatory properties of eucalyptus oil (EO) and its principle component eucalyptol (1,8- cineole) ( Santos and Rao, 2000 ; Silva et al, 2003 ; Sadlon and Lamson, 2010 ; Yadav and Chandra, 2017 ), which, depending on the source species of eucalyptus, accounts for up to 75% of eucalyptus oil’s content ( Aziz et al, 2019 ). Essential oils of various eucalyptus species are utilized in the cosmetic, food, and pharmaceutical industries ( Marzoug et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…The formed transparent solution of the micelle structure represents ultra‐small micelles formation that is dispersed in the aqueous phase. The very small size of the formed micelle is due to the addition of the oil‐soluble D‐limonene that could easily homogenize the formed aggregates of the surfactants and facilitate the diffusion of the surfactant in the aqueous phase (Aziz et al, 2019; Chang et al, 2013; Chang & McClements, 2014; Kuznetsova et al, 2020). Moreover, the utilization of the ultrasonication has additional assistance to ease the formation of ultrasmall micellar structure (Li & Chiang, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Hot plate test in rats is one of in vivo analgesic study that assessed by measuring the rats’ pain responses toward thermal stimulus after being put on top of the hot plate (Aziz et al. 2019 ). Rats exposed to NLCs and LPNs were subjected to the hot plate test to determine the effects on pain relief compared with free drugs.…”
Section: Discussionmentioning
confidence: 99%